(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Every ophthalmic surgeon who performs penetrating Keratoplasty has experienced the disappointment felt by patient and physician alike when a technically successful corneal graft fails. Despite the advances that have been made in corneal preservation and surgical technique, a significant proportion of grafts eventually fail. Objective: To compare frequency of graft failure after penetrating Keratoplasty with Optisol preserved cornea in two groups i.e. cornea preservation time less than 7 days versus cornea preservation time from 7 to 14 days Study Design: Randomized control trial Study Setting: Department of Ophthalmology, FMU Allied Hospital Faisalabad Study Duration: 6 months after approval of the synopsis From: June 2024 to November 2024 Methodology: Informed consent was taken from all patients. Patient fulfilling the inclusion criteria were enrolled from OPD of Ophthalmology unit. Detailed history and physical examination was done. Patients were divided in two groups by lottery method. Patients in Group A were grafted with corneas preserved in Optisol medium within 7 days and Patients Group B were grafted with corneas preserved in Optisol medium from 7 to 14 days after harvesting from the donor. All corneal grafts were done by single surgical team under standard surgical procedure. Post-operative care was done for all patients according to standard protocols of hospital. Patients were examined for graft failure at follow-up visit at 12 weeks after cornea graft procedure. Results: In this study, mean age was 50.8+8.59 years in Group-A and 48.35+9.57 years in Group-B, 65%(n=26) Patients in Group-A and 60%(n=24) Patients in Group-B were male and 35%(n=14) in Group-A and 40%(n=16) in Group-B were females. Comparison of graft failure shows 7.5%(n=3) in Group-A and 47.5%(n=19) in Group-B had graft failure whereas 92.5%(n=37) in Group-A and 52.5%(n=21) in Group-B had no graft failure, (p value of 0.00006.) Conclusion: Cornea preservation in Optisol medium within 7 days had significantly lower rate of graft failure when compared with cornea preservation time of 7 to 14 days in cases undergoing penetrating Keratoplasty.